A Simple Method for Endoscopic Treatment of Large Gastric Phytobezoars: “Hand-Made Bezoaratome” - Toka, Bilal; Eminler, Ahmet Tarik; Karacaer, Cengiz; Uslan, Mustafa Ihsan; Koksal, Aydin Seref; Parlak, Erkan (Turkish Journal of Gastroenterology, 2021)
Background/Aims: Large gastric phytobezoars are generally resistant to standard chemical or endoscopic treatments. We presented our experience of an alternative endoscopic method using a hand-made tool called a “hand-made bezoaratome” for the treatment of large gastric phytobezoars.Patients and Methods: Patients consulted or diagnosed with gastric bezoars at Education and Research Hospital between January 2015 and December 2018 were prospectively included in the study. Patients with phytobezoars of 50 mm and larger were included in the study. Patients with trichobezoars, lactobezoars, pharmacobezoars, under 18 years of age, and pregnant women were excluded. A 0.25 mm diameter guidewire and a mechanical lithotripter sheath were used to prepare the ‘’hand made bezoaratome’’. After the first procedure, patients were advised to consume 2500 ml of Coca Cola® or the same amount of pineapple juice per day, until the next procedure. Endoscopic procedures were performed at 5-day intervals until complete reabsorption of the bezoar was achieved. Patients were followed up for six weeks.Results: The study group included 37 (21 males, mean age: 57,6 ± 12,5 years) patients. The median size of the phytobezoars was 71 (50-90) mm. The median endoscopic procedure time was 853 (380-1940) seconds. The success rate for endoscopic fragmentation was found to be 100 %. No major complications occurred during the endoscopic procedures, but one patient (2.7%) required surgery for ileus due to an obstruction at the distal part of the jejunum, 61 hours after the second endoscopic session. The overall success rate of the endoscopic treatment was 97.3 %. Conclusion Using a “hand-made bezoaratome” is effective and reliable for the endoscopic treatment of large gastric bezoars.